SN Video coding and web development. - Groot, Coen de (SN Video Coding and Web Development, 2020)
In this video course you will learn how to write simple programs in the popular and powerful Python programming language. You'll start by looking at how to install Python, and how to create and run simple Python scripts. You will then learn how to store and operate on information. You will see how to combine strings, split them up and search in strings, all with some very simple commands. We also explain how to work with numbers, such as adding or multiplying them. You will also see the different ways to store collections of values, for instance as a list or a dictionary. Next we explain how to control the flow of your program. You will discover how to make decisions and respond to different values ('if') and how to do the same thing many times ('for' and 'while'). To make it very practical you will learn how to manipulate files and spreadsheets. And to help you write larger programs and tackle more complicated tasks you will see how to split your program into simple steps. Learn to tap into the power of Python and its many libraries in one and a half hours.